Upaya Penanganan Herpes Zooster pada Pasien Perempuan Usia 40 Tahun melalui Pendekatan Kedokteran Keluarga di Puskesmas Nisam Kabupaten Aceh Utara - Asna Safitri; Noviana Zara (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Herpes zoster is a skin infection caused by the reactivation of the varicella-zoster virus, characterized by unilateral skin lesions corresponding to dermatome distribution and complaints of pain or itching. This disease is more common in adults and the elderly, especially in individuals with reduced immunity due to stress or work overload. A case was reported of a 40-year-old woman who worked as a nurse and came to a primary health care facility complaining of itching and red spots on her right breast area that had spread to the surrounding area two weeks before the examination and had worsened in the last few days. Physical examination revealed unilateral red skin lesions in a dermatomal pattern without crossing the midline of the body, consistent with the early phase of herpes zoster. Management was comprehensive, including medication, patient education about the disease and skin care, prevention of complications, and family support. A holistic approach is necessary to improve the success of therapy and the patient’s quality of life.